Strengthening Service Leadership and Self-Efficacy in Increasing Job Satisfaction of Private Junior High School Teachers - Eko Pramono; Taty Rahayuningsih; Lisa Chandrasari Desianti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
The purpose of this study was to find a way to increase teacher job satisfaction by examining the relationship between servant leadership and self-efficacy and job satisfaction. The population in this study were honorary teachers at private junior high schools throughout Bogor Regency, which opened 160 teachers. The sample was determined by simple random sampling, using the proportional random sampling technique and the Taro Yamane formula so that the number of samples in this study was 113 teachers. The method in this study is a statistical correlational method with a quantitative approach. The correlational approach is used to determine whether or not there is a relationship between the independent variable and the dependent variable. Collecting data in this study using a questionnaire or questionnaire. This study has two independent variables and one dependent variable. The independent variables are service leadership (X1) and self-efficacy (X2), while the determining variable is teacher job satisfaction (Y). This study obtained the results that there is a positive and significant relationship between service leadership (X1) and teacher job satisfaction (Y) with a correlation coefficient of 0.527, and there is a positive and significant relationship between self-efficacy (X2) and teacher satisfaction (Y) with the correlation coefficient value is 0.449, and there is a relationship between service leadership (X1) and self-efficacy (X2). Together, there is a positive and significant relationship with teacher job satisfaction (Y) at Private Junior High Schools in Bogor Regency with a correlation coefficient (R) of 0.543. Based on this, it can be stated that to increase teacher job satisfaction, it can be supported through efforts to increase service leadership and self-efficacy.